The Case of the Missing Muscles. - Silbert Aumiller, Mira; Gallaway, Michael; Bailey, Jo Ann T. (Optometry & Visual Performance, 2015)
Background: Congenital absence of the superior oblique (SO) is a rare cause of strabismus. It should be suspected in a patient with a presumed diagnosis of SO palsy presenting with amblyopia, an unusually large vertical deviation, and a significant horizontal deviation. Case Report: We report a case of an infant presenting at five months of age with a significant right head tilt since birth and significant vertical and horizontal strabismus. The patient was not meeting developmental milestones. The infant was referred for surgery, where it was discovered that she had a congenital lack of SO muscles. After surgery, the patient was treated with amblyopia therapy and vision therapy and followed for six years. Surgical and non-surgical intervention led to a good visual outcome, enhanced achievement of developmental milestones, and improved cosmesis. Conclusion: Although absence of SO muscles is a rare etiology for torticollis and strabismus, it should be considered in cases of early and significant ocular misalignment. The presence of horizontal and vertical strabismus in a patient with a presumed congenital SO palsy should raise suspicion of an absent SO. Early intervention can make a significant difference for the patient in terms of both visual outcome and cosmesis. This patient is the youngest documented case of SO aplasia and the first published case using surgery and vision therapy in combination.